Pengaruh Pembelajaran Bahasa Indonesia Berbantuan Media Pembelajaran dengan Aplikasi Focusky Terhadap Motivasi dan Hasil Belajar Siswa Kelas V di SD Negeri 09 Kepahiang - Aidi, Rohman; Muktadir, Abdul; Susanta, Agus (Jurnal Kajian Pendidikan Dasar, 2025)
This study aims to determine the effect of learning Indonesian assisted by focusky media on the motivation and learning outcomes of fifth grade students at elementary school09 Kepahiang. This type of research is a quantitative research with quasi-experimental methods. The population in this study were fifth grade students at elementary school 09 Kepahiang. The research instrument was a learning motivation questionnaire sheet and learning achievement test questions. The data analysis technique used is quantitative analysis. Processing and analysis of the data carried out included determining the score of descriptive analysis questions, analysis of prerequisite tests, and inferential analysis. The results showed that the results of the learning motivation hypothesis test showed that the value of tcount using Equal Variations Assumed = 3.033 and the value of Sig. (2-tailed) has a value of 0.004 and the ttable distribution value is 2.011. So that tcount> ttable (3.033 > 2.011) and Sig.(2-tailed) 0.004 <0.05. The results of the hypothesis test show that the value of tcount using Equal Variances Assumed = 2.859 and the value of Sig. (2-tailed) has a value of 0.006 and the ttable distribution value is 2.011. So that tcount> ttable (2.859 > 2.011) and Sig.(2-tailed) 0.006 <0.05. Based on the results of this study it can be concluded that there is a significant influence of Indonesian language learning assisted by focusky media on the motivation and learning outcomes of fifth grade students at elementary school09 Kepahiang.